2013
DOI: 10.1002/pbc.24843
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure abnormalities in children with sickle cell anemia

Abstract: Blood pressure abnormalities are common in adolescents with SCA and are a possible modifiable risk factor in the progression of sickle cell nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
7
34
2
Order By: Relevance
“…While in-clinic BP is convenient and may portend clinical complications, the gold standard strategy for identifying risk for end-organ damage in other disease has been to perform 24 hour ABPM [20]. Our cohort confirms prior pediatric studies that demonstrate a lack of correlation between hypertension defined by in-clinic BP monitoring and 24 hour ABPM [21, 35]. In addition, our cohort mirrors the results of two prior studies which suggested that SCA patients have a higher prevalence of nocturnal hypertension and lack of nocturnal dipping in pediatric SCA [21, 22].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…While in-clinic BP is convenient and may portend clinical complications, the gold standard strategy for identifying risk for end-organ damage in other disease has been to perform 24 hour ABPM [20]. Our cohort confirms prior pediatric studies that demonstrate a lack of correlation between hypertension defined by in-clinic BP monitoring and 24 hour ABPM [21, 35]. In addition, our cohort mirrors the results of two prior studies which suggested that SCA patients have a higher prevalence of nocturnal hypertension and lack of nocturnal dipping in pediatric SCA [21, 22].…”
Section: Discussionsupporting
confidence: 76%
“…Ambulatory blood pressure monitoring (ABPM), which identifies nocturnal hypertension, is superior to casual in-clinic blood pressure monitoring for identifying children at high risk for end-organ damage [20]. Two prior studies have identified a high prevalence of nocturnal hypertension in SCA, yet no data are available to define the association between nocturnal hypertension and eGFR in SCA [21, 22]. Hyperuricemia has been associated with hypertension and cardiovascular events in other diseases but, despite the high prevalence of hyperuricemia in SCA, the association of hyperuricemia and sickle cell nephropathy has not been explored [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Our prevalence is similar to that of 45% reported by Benneh-Akwasi Kuma et al in Ghana [20] as well as of 44% found by Makubi et al [21] and Gordeuk et al [6]. However, it is somewhat higher than that of 17% found by Becker et al [5] and Bodas et al [4], respectively. The observed disparity in relative hypertension prevalence could be explained by differences in methodology, patient's clinical characteristics and thresholds used to define relative hypertension.…”
Section: Discussioncontrasting
confidence: 46%
“…Although elevated PP is a marker of arterial stiffness in old people, the association of PP and relative hypertension might be related to increased stroke volume as a compensatory mechanism, similar to that seen in patients with clinical hemolytic anemia [1]. Using ambulatory blood pressure monitoring (ABPM) in SCD patients, Becker et al [5] reported a 35% and 56% prevalence of unrecognized hypertension and non-dipping blood pressure pattern, respectively. They concluded that BP abnormalities in SCD are more common than usually reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation